Análise e melhoria de processos críticos de TI em uma indústria de alimentos - Oliveira, Márcio Luis de (Universidade do Vale do Rio dos Sinos, 2012)
In the last ten years many research works have been made about the subject of business process management, pointing it as an efficient way of reaching positive results through revision and improvement of company processes. Also, more and more the companies are being challenged to get better results using less resources, and to present a much more clear and efficient administration. The Information Technology has an important role on this objective, because it can help organizations to review their processes and this way, reinforce the implementation of corporate governance concepts through IT governance. To answer these challenges, the IT organization has arranged their processes in a way that is more aligned with the business needs. Under this context that this research was developed, with the objective of getting a pragmatically view of the application of the business process management concepts in the analysis and improvement of the IT processes in a food industry.
Keywords: Gestão de processos de negócio; Tecnologia da Informação; Governança de TI; Business process management; Information technology; IT Governance